ANIMASI PROSES PENGIRIMAN SMS PADA GSM MENGGUNAKAN MCROMEDIA FLASH MX - Pratama, Suenda Adi; Setyanto, Budi (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Negeri Semarang, 2009)
One of popular services in GSM (Global System for Mobile Communication) system is SMS (Short Message Service). Beside of the low delivery cost, SMS also allows notification and alert delivery. SMS has good and important role in telecommunication world, so the understanding about SMS technology is very needed. Looking for a good method to help about SMS technology understanding until right know is rarely, especially about SMS delivery process. This project aims to create an animation of SMS delivery process on GSM system using Macromedia Flash MX, so hopefully could help to study about SMS delivery process. The SMS animation delivery program with Macromedia Flash MX could demonstrate three processes in SMS delivery mechanism, such as SMS delivery success, delay and fail, but can not demonstrate the signal process and the conversion message with detail.Keyword : GSM, Macromedia Flash MX, SMS